Possible link between weight change and dementia queried. (2nd August 2019) - Palmer, Sarah
Abstract : Maintaining a healthy weight can reduce the risk of many health conditions. A recent Korean study seems to establish a link between weight increases or decreases and dementia, but Alzheimer's Research UK is sceptical.